2006
DOI: 10.1007/s10162-006-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Coding by Cochlear Nucleus Bushy Cells in DBA/2J Mice with Early Onset Hearing Loss

Abstract: The bushy cells of the anterior ventral cochlear nucleus (AVCN) preserve or improve the temporal coding of sound information arriving from auditory nerve fibers (ANF). The critical cellular mechanisms entailed in this process include the specialized nerve terminals, the endbulbs of Held, and the membrane conductance configuration of the bushy cell. In one strain of mice (DBA/2J), an early-onset hearing loss can cause a reduction in neurotransmitter release probability, and a smaller and slower spontaneous mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…Although it is clear that deafferentation perturbs cellular properties throughout the central auditory system (Kotak and Sanes, 1996;Vale and Sanes, 2000;Kotak et al, 2005;Walmsley et al, 2006;Wang and Manis, 2006), the effect of sound attenuation has not been established. Because there is considerable debate about the behavioral impact of conductive hearing loss alone (Feagans et al, 1987;Teele et al, 1990;Mody et al, 1999;Psarommatis et al, 2001;Roberts et al, 2002;Paradise et al, 2005), it is essential to establish whether or not central deficits occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is clear that deafferentation perturbs cellular properties throughout the central auditory system (Kotak and Sanes, 1996;Vale and Sanes, 2000;Kotak et al, 2005;Walmsley et al, 2006;Wang and Manis, 2006), the effect of sound attenuation has not been established. Because there is considerable debate about the behavioral impact of conductive hearing loss alone (Feagans et al, 1987;Teele et al, 1990;Mody et al, 1999;Psarommatis et al, 2001;Roberts et al, 2002;Paradise et al, 2005), it is essential to establish whether or not central deficits occur.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have shown that temporal processing is disrupted by hearing loss, but they do not distinguish between changes that may occur in the brainstem (Wang and Manis, 2006) and those that occur at higher centers. Direct examination of the synaptic or biophysical properties that subserve temporal processing can be revealed by direct examination of a specific area of the auditory CNS.…”
Section: Hearing Loss Perturbs Temporal Precisionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the presence of a primary-like peristimulus spike-time histogram to tone bursts in vivo, the spike patterns of a bushy cell may not faithfully reflect the presynaptic activity of a given ANF (Kopp-Scheinpflug et al 2002) due to several factors. These include the convergence of ANFs onto bushy neurons (Leao et al 2005;Liberman 1991;Nicol and Walmsley 2002;Rothman et al 1993;Ryugo and Parks 2003;Xu-Friedman and Regehr 2005a,b), the effects of inhibition from the dorsal cochlear nucleus (DCN) and superior olivary complex (Caspary et al 1994;Wickesberg and Oertel 1988), activitydependent modulation of presynaptic release probability (Brenowitz and Trussell 2001a;Turecek and Trussell 2001), and synaptic depression during high rates of activity (Oleskevich et al 2000;Wang and Manis 2006;Xu-Friedman and Regehr 2005b;Yang and Xu-Friedman 2008;Zhang and Trussell 1994). More recently, recordings from presumed AVCN spherical bushy cells in vivo have suggested that as many as 50% of ANF spikes may fail to drive bushy cells (Kopp-Scheinpflug et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The calyx of Held synapses in the auditory brainstem do show synaptic depression and facilitation (reviewed in Xu et al, 2007), although apparently these effects are smaller in the cochlear nucleus of mature animals (Wu and Oertel, 1987;Brenowitz and Trussell, 2001). Relatively small effects are seen in bushy cells (Wang and Manis, 2006); in non-bushy cells, depression and facilitation seem to overlap, giving a small net effect (MacLeod et al 2007). In addition, there are important differences between in-vivo and slice experiments (Hermann et al, 2007).…”
Section: Lack Of Short-term Synaptic Plasticitymentioning
confidence: 99%